Synody w Afryce Prokonsularnej III wieku jako przejaw kolegialności biskupów w świetle Kanonów synodalnych i Listów św. Cypriana z Kartaginy - Strękowski, Stanisław (Vox Patrum, 2019)
In the mid-third century, Thascius Caecilius Cyprianus, a wealthy and educated man, was elected bishop of Carthage in proconsular Africa. During the persecution ordered by Emperor Decius, the faith of many people was put to the test. Disciplinary and administrative divisions arose in the Christian community. St. Cyprian appealed to the old tradition cultivated not only in the Church of proconsular Africa, but also in other provinces of the universal Church, which was the convening of synods in order to solve together pastoral problems. During the time of sitting on the episcopal capital in Carthage, a total of 7 synods were convened, whose participants took their stand on the schism of Felicissimus and Novatian, and on the return to the church community of persons who were subject to the decree of Decius by making idolaters, the validity of baptism by heretics and baptism children. This study is an attempt to show the important role of synods in shaping the collegiality of bishops in proconsular Africa in the mid-third century in the context of concern for the unity of the Church.